Clinical, Endoscopic and Pathological Characteristics of Colorectal Polyps in Children and Adolescents - Moeen Ul Huq, Sameen Arif Saeed, Muhammad Zain Akhtar, Rizwan Ur Rehman, Ahmed Aftab, Rosheena Afridi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Polyps of the gastrointestinal tract (GI) are apparent protrusions from the mucosal surface. The majority of polyps is asymptomatic and goes unnoticed; however in symptomatic situations, the most common clinical manifestations include abdominal discomfort, and rectal prolapse, intestinal blockage, and GI bleeding. The present study intended to assess the colorectal polyps characteristics based on clinical, pathological, and endoscopy in children and adolescents. Patients and Methods: This retrospective study was conducted on 78 children and adolescents (<18 years) with colorectal polyps in Gastroenterology Department of DHQ Teaching Hospital and Mufti Mahmood Memorial Hospital, Dera Ismail Khan from January 2020 to September 2022. Participants were assessed for various clinical variables such as age, gender, colonoscopy-related signs and symptoms, polyp identification, symptom’s onset age, duration between colonic polyp’s endoscopic diagnosis and symptoms onset, and intestinal polyps family history. Polyp’s characteristics involved: frequency, histology, morphological type, and distribution. SPSS version 26 was used for data analysis. Results: The overall mean age was 8.6±2.4 years with an age range 3 to 18 years. Of the total 78 colonic polyps, there were 48 (61.5%) male and 30 (38.5%) females. The most prevalent symptom was rectal bleeding present in 94.6% (n=74) cases with 13.8±16 months. Juvenile was the prevalent polyps found in 76.9% (n=60), out of which 96.7% (n=58) were in left colon. The prevalence of Solitary polyps, multiple polyps, familial adenomatous polyposis, and Peutz-Jeghers syndrome (PJS) was 10.3% (n=8), 6.4% (n=5), 3.8% (n=3), and 2.6% (n=2) respectively. Polyposis syndrome cases were more likely to have old age, diarrhea, anemia, and abdominal pain. Peutz-Jeghers syndrome majority patients experienced intestinal partial blockage with acute episodes, abdominal pain, and emergency laparotomy, resulting in increased morbidity. Conclusion: The present study found that clinical signs of polyposis syndrome include anemia, diarrhea, abdominal pain, polypectomy history, and older age at presentation. Despite the fact that the most commonly diagnosed kind of polyp was juvenile colonic polyps, the current investigation recognized a substantial number of polyposis syndromes children, which are related with individual’s higher rate of morbidity. Keywords: Colonic polyps, Clinical features, Endoscopic characteristics, Colonoscopy